CONSEQUENCES OF PROTEIN BASED FOAMING AGENT ON LIGHTWEIGHT CONCRETE - Mr. VIKRAM V.MULE, MR.MARUTI S.BHOSALE (International Journal of Innovations in Engineering Research and Technology, 2022)
The main objective of this project is to develop traditional or conventional concrete and simultaneously motivate the people about light weight concrete. This focuses on tests such as Compressive test, Water absorption, and flexural test only. The results obtained are interesting and useful to compare the results with that of traditional concrete. The main fortes of this concrete is to low density and thermal conductivity, Ultimately there is reduction of dead load, faster building rate in construction and lessen haulage and handling costs.